2018
DOI: 10.1097/pas.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

PRAME Expression in Melanocytic Tumors

Abstract: PRAME (PReferentially expressed Antigen in MElanoma) is a melanoma-associated antigen that was isolated by autologous T cells in a melanoma patient. While frequent PRAME mRNA expression is well documented in cutaneous and ocular melanomas, little is known about PRAME protein expression in melanocytic tumors. In this study we examined the immunohistochemical expression of PRAME in 400 melanocytic tumors, including 155 primary and 100 metastatic melanomas, and 145 melanocytic nevi. Diffuse nuclear immunoreactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
477
10
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(573 citation statements)
references
References 20 publications
45
477
10
6
Order By: Relevance
“…The sensitivity of diffuse PRAME expression for MM in our cohort is consistent with the findings of Lezcano et al 4 Given the rarity of CCS, our study is limited by the small number of these cases. Through several observations, some investigators conclude that the loss of 5-hmC is because of downregulation of the enzymatic conversion from 5-mC.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The sensitivity of diffuse PRAME expression for MM in our cohort is consistent with the findings of Lezcano et al 4 Given the rarity of CCS, our study is limited by the small number of these cases. Through several observations, some investigators conclude that the loss of 5-hmC is because of downregulation of the enzymatic conversion from 5-mC.…”
supporting
confidence: 92%
“…3 With the identification of this biomarker, efforts to produce a reliable immunohistochemical stain developed and subsequent studies have reported that 5-hmC immunohistochemistry is a useful diagnostic tool in evaluating various melanocytic lesions. [4][5][6] However, there are only few studies examining expression of 5-hmC in spitzoid lesions. Those that do, have observed that…”
mentioning
confidence: 99%
“…The following two parameters were documented for PRAME immunohistochemistry: (i) the staining pattern in TCs (cytoplasmic and/or nuclear); and (ii) the percentage of positive TCs (number of PRAME‐positive TCs/total number of TCs). Immunohistochemical analysis of PRAME was performed as described previously . PRAME immunopositivity was defined as any immunolabelling within the tumour.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis of PRAME was performed as described previously. 26 PRAME immunopositivity was defined as any immunolabelling within the tumour. Finally, the percentage of TCs (number of positive TCs/total number of TCs) showing membranous immunopositivity of MHC I was recorded and divided into three categories: positive (≥75% of TCs), heterogeneous (25-74% of TCs), and negative (<25% of TCs).…”
Section: M M U N O H I S T O C H E M I S T R Y a N D S C O R I N G mentioning
confidence: 99%
“…Recent studies by Lezcano et al characterized PRAME immunohistochemistry in a variety of melanocytic tumors, including benign melanocytic nevi, primary and metastatic melanoma, melanoma in situ, nodal nevi, and other benign melanocytic proliferations. 14,15 This valuable work highlighted the utility of PRAME immunohistochemistry in melanoma diagnosis via examination of largely histopathologically unequivocal benign and malignant melanocytic proliferations.…”
mentioning
confidence: 98%